Effects of nanostructured essential oils against subterranean termites (Coptotermes gestroi). (23rd January 2018) - Clerici, D. J.; de Souza, M. E.; Quatrin, P. M.; Vianna Santos, R. C.; Costa‐Leonardo, A. M.; Ourique, A. F.; Raffin, R. P.; Marques, C. T.; de Camargo Dietrich, C. R. R.; de Silva Gündel, S.; Klein, B.; Wagner, R.
Abstract: Currently, the control of termites is mainly carried out with the use of chemical pesticides, which although effective, pose risks to the environment and to human beings. An alternative to using such chemical pesticides is natural products such as essential oils in insecticidal action. Despite the fact of being effective, essential oils are unstable, poorly soluble in water, and degrade from the action of light, oxygen even at moderate temperatures. Thus, the nanostructuring of essential oils could circumvent such problems and ensure its effectiveness. The following study aimed to assess for the first time the effects of nanostructured systems of essential oils of Cymbopogon flexuosus, Eucalyptus globulus and Melaleuca alternifolia in subterranean termites ( Coptotermes gestroi ). The results showed that the solid lipid nanoparticles of M. alternifolia have both repellent and insecticide action. The following study showed that nanostructuring of essential oils with insecticidal action is a promising tool in the fight against termites.